2019
DOI: 10.1103/physrevd.99.126015
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of asymptotic safety for quantum gravity

Abstract: We study fixed points of quantum gravity with renormalisation group methods, and a procedure to remove convergence-limiting poles from the flow. The setup is tested within the f (R) approximation for gravity by solving exact recursive relations up to order R 70 in the Ricci scalar, combined with resummations and numerical integration. Results include fixed points, scaling exponents, gap in the eigenvalue spectrum, dimensionality of the UV critical surface, fingerprints for weak coupling, and quantum equations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
129
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(144 citation statements)
references
References 135 publications
(310 reference statements)
15
129
0
Order By: Relevance
“…This UV fixed point would make the theory UV finite and thus non-perturbatively renormalizable. Starting with the seminal work by Reuter [15], a lot of evidence was collected in favour of this scenario [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The interplay of quantum gravity and matter was extensively investigated as well [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…This UV fixed point would make the theory UV finite and thus non-perturbatively renormalizable. Starting with the seminal work by Reuter [15], a lot of evidence was collected in favour of this scenario [16][17][18][19][20][21][22][23][24][25][26][27][28][29]. The interplay of quantum gravity and matter was extensively investigated as well [30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…At least in the matrix-model case, multi-trace interac- tions actually encode higher-order curvature terms, see, e.g., [100,101]. Results in continuum studies of asymptotically safe gravity suggest that higher-order curvature terms are relevant, see, e.g., [70,72,73,[102][103][104][105][106][107]. We therefore tentatively suggest that including multitrace interactions might be important to escape the branched polymer phase.…”
Section: Interacting Fixed Pointmentioning
confidence: 78%
“…At this stage, it is instructive to compare the results (3.14) to the ones obtained from solving the Wetterich equation (2.1) projected onto gravitational actions of f (R)-type [31,32,51]. Performing a polynomial expansion of f (R) N n=0ū n R n , the eigenvalues of the stability matrix (2.5) have been determined for successively increasing values N = 6 [31,32], N = 8 [121], N = 35 [40,41], and lately also N = 71 [113]. Building on previous investigations [40,41], ref.…”
Section: Comparison To the Polynomial F (R)-truncationmentioning
confidence: 99%
“…Building on previous investigations [40,41], ref. [113] reported that for large values of n the real parts of the eigenvalues λ n follow an almost Gaussian behavior λ f (R) n ≈ a n − b , (3.17) where the best-fit values for the parameters a and b are a = 2.042 ± 0.002 , b = 2.91 ± 0.05 . (3.18) In order to connect the results (3.17) and (3.14) we follow the strategy outlined in [25].…”
Section: Comparison To the Polynomial F (R)-truncationmentioning
confidence: 99%